Youth empowerment in non-timber forest products (NTFPs) of sub-Saharan Africa: the role of corporate social responsibility in Niger Delta, Nigeria. Issue 5 (29th November 2019) - Uduji, Joseph Ikechukwu; Okolo-Obasi, Elda Nduka
Abstract : Purpose: The purpose of this paper is to critically examine the multinational oil companies' (MOCs') corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of Global Memorandum of Understandings (GMOUs) on rural young people involved in non-timber forest products (NTFPs) for sustainable livelihood in Niger Delta, Nigeria. Design/methodology/approach: Data for this study were collected from primary sources, using participatory rural appraisal technique of semi-structured interview questionnaire. The use of participatory research techniques in collecting CSR impact data especially as it concerns the rural young people is because it involves the people being studied, and their views on all the issues are paramount. Both descriptive and inferential statistics were used to analyse the data. Inferential statistical tool – estimation of logit model was used to test the two research hypothesis. Findings: The results indicate that GMoUs have not given adequate attention to young people as a special target sub-group who live in rural areas and depend mostly on NTFPs. Results also show that a number of factors hindering rural young people from the use and development of NTFPs include a policy vacuum, non-destructive harvesting, and destruction of natural habitats, bushfires, population growths and high demands. Research limitations/implications: The semi-structured interview questionnaire was directly administered by the researchers with the help of research assistants. The use of local research assistants was because of the inability of the researchers to speak the different local languages and dialects of the many ethnic groups of Ijaws, Ogonis, Ikweres, Etches, Ekpeyes, Ogbas, Engennes, Obolos, Isokos, Nembes, Okirikas, Kalabaris, Urhobos, Iteskiris, Igbos, Ika-Igbos, Ndonis, Orons, Ibenos, Yorubas, Ibibios, Anangs, Efiks, Bekwarras, Binis, Eshans, Etsakos, Owans, Itigidis, Epies, Akokoedos, Yakkurs, etc., in the sampled rural communities. Practical implications: An appropriate GMoU-intervention framework for sustainable promotion of NTFPs, domestication of NFTPs, improving harvesting and processing techniques are necessary to facilitate good security, reduction of poverty and improved livelihoods, particularly for the economically-marginalized and forest-dependent rural young people is imperative. Social implications: Sustainable livelihoods of the forest-dependent rural young people in sub-Saharan Africa would require some focussed CSR interventions on the NTFPs for sustainable livelihood. Facilities pertaining to storage, grading, processing and value addition through the convergence of existing schemes and programmes should be promoted and created. MOCs are in a position to empower the rural young people with information about the market, policy and products to enable the rural people strategizing and accessing returns from NTFPs in sub-Saharan Africa. Originality/value: This research adds to the literature on multinational enterprises' CSR initiatives in developing countries and rationale for demands for social projects by host communities. It concludes that business has an obligation to help in solving problems of sustainable livelihood.